2014
DOI: 10.3133/ofr20141251
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in birds of San Francisco Bay-Delta, California: trophic pathways, bioaccumulation, and ecotoxicological risk to avian reproduction

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 72 publications
(108 reference statements)
3
25
0
Order By: Relevance
“…Thus, while the study results are useful for highlighting areas of potential future research, they are not sufficiently conclusive to support identification of NOAELs or LOAELs for TRV derivation purposes. The Great Salt Lake study also reported no evidence of adverse effects of Hg on American avocets ( Recurvirostra americana ), black‐necked stilts ( Himantopus mexicanus ), or Forster's terns, all of which were subject to lower Hg exposures than those identified for the same species in San Francisco Bay (see Table ).…”
Section: Literature Review Resultsmentioning
confidence: 95%
“…Thus, while the study results are useful for highlighting areas of potential future research, they are not sufficiently conclusive to support identification of NOAELs or LOAELs for TRV derivation purposes. The Great Salt Lake study also reported no evidence of adverse effects of Hg on American avocets ( Recurvirostra americana ), black‐necked stilts ( Himantopus mexicanus ), or Forster's terns, all of which were subject to lower Hg exposures than those identified for the same species in San Francisco Bay (see Table ).…”
Section: Literature Review Resultsmentioning
confidence: 95%
“…In places where rice is the dominant land use, export of MeHg in rice drainage waters can potentially have large impacts on water quality. Methylmercury in surface water can bioaccumulate in wildlife, reaching levels in sport fish that are a concern for human health, and negatively affecting wildlife fitness (Chan et al, 2003; Crump and Trudeau, 2009; Ackerman et al, 2014). Little is known about Hg biogeochemical cycling in rice fields or soil and water fluxes (Rothenberg et al, 2014).…”
mentioning
confidence: 99%
“…Export of MeHg from rice fields is a concern in the Sacramento Valley, California, where rice is grown on 240,000 ha of the valley (USDA‐NASS, 2016), and Hg and gold mining resulted in Hg contamination in the surrounding mountains (Churchill, 2000; Rytuba, 2003; Alpers et al, 2016). Downstream in the Sacramento‐San Joaquin Delta (hereafter referred to as the “Delta”), MeHg concentrations are elevated and negative impacts of Hg on wildlife have been documented (Ackerman et al, 2014). Both field‐scale and watershed‐scale studies report rice field drainage waters have elevated MeHg concentrations and/or loads during the fallow season (Alpers et al, 2014; Bachand et al, 2014; Eagles‐Smith et al, 2014; Tanner et al, 2017), when fields are flooded to decompose rice straw.…”
mentioning
confidence: 99%
“…Methylmercury exposure is a significant concern for special-status bird species, including the federally endangered Ridgway's Rail (Rallus obsoletus) and California Least Tern (Sternula antillarum browni). Forster's Tern (Sterna fosteri) is the species at greatest risk: Ackerman et al (2014) found that 79% of eggs from this species were above a high-risk threshold of 1 μg g -1 fresh wet weight. The control plans for mercury in both the Bay and the Delta (SFBRWQCB 2006;Wood et al 2010) include a concentration target for prey fish to protect piscivorous birds.…”
Section: A Synthesis Of Specific Bay-delta Contaminants Metals and Mementioning
confidence: 99%